2021
DOI: 10.38042/biotechstudies.932937
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers for lung adenocarcinoma identified by integrative transcriptomics analysis

Abstract: How to CiteKasavi, C. (2021). Potential biomarkers for lung adenocarcinoma identified by integrative transcriptomics analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…FHL2 was identified initially as a biomarker of lung adenocarcinoma and has been confirmed to function as an oncoprotein in human LC. 17,18 However, until now, there is still no report that revealed the detailed role of FHL2 in NSCLC. In this research, we preliminarily explored the efficacies of FHL2 on NSCLC both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FHL2 was identified initially as a biomarker of lung adenocarcinoma and has been confirmed to function as an oncoprotein in human LC. 17,18 However, until now, there is still no report that revealed the detailed role of FHL2 in NSCLC. In this research, we preliminarily explored the efficacies of FHL2 on NSCLC both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Al‐Nomani et al found that there was a close association between lymphatic metastasis and enhanced FHL2 expression in sporadic colorectal cancer 16 . Importantly, FHL2 wasdescribed previously as a biomarker of lung adenocarcinoma and was recorded to be working as an invasion‐promoting gene facilitating the progression and metastasis of human LC 17,18 . Nevertheless, the effects of FHL2 on NSCLC still remains under investigated to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation